2017
DOI: 10.1186/s13195-017-0256-8
|View full text |Cite
|
Sign up to set email alerts
|

Antipsychotic prescribing for Alzheimer’s disease and related disorders in specialized settings from 2010 to 2014 in France: a repeated cross-sectional study

Abstract: BackgroundSafety warnings from health authorities are currently intended to limit the use of antipsychotics (APs) in dementia-related conditions to treat neuropsychiatric symptoms, such as disturbing and/or delusional behaviors. The aim of this study is to investigate prevalence, correlates and trends of AP prescribing among people with dementia between 2010 and 2014 in the French population.MethodsAP prescribing and associated factors among individuals with AD, mixed dementia and vascular dementia in the Fren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
2
9
3
Order By: Relevance
“…We did not find any association between age and AP prescription while previous studies showed that overall antipsychotic use is significantly lower for older patients 16,35,36…”
Section: Discussioncontrasting
confidence: 94%
See 2 more Smart Citations
“…We did not find any association between age and AP prescription while previous studies showed that overall antipsychotic use is significantly lower for older patients 16,35,36…”
Section: Discussioncontrasting
confidence: 94%
“…Some studies found that women were more frequently prescribed APs than men 2931. However, consistent with findings from some other studies,16,32,33 in our study men were more likely than women to be prescribed with APs. A recent review by Trenaman et al34 observed that men and women tend to use more antipsychotics dependent on their living environment, women in the community and men in long-term care facilities.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Antipsychotic medications are the first-line pharmacological intervention for severe mental illnesses (SMI) such as schizophrenia [ 1 , 2 ] and other psychoses, while also being used to relieve distress and to treat neuropsychiatric symptoms in dementia [ 3 ]. Oral antipsychotic medication prescribed in primary care is one of the main sources of support to people with a history of psychosis.…”
Section: Introductionmentioning
confidence: 99%
“…Antipsychotic medications are the first-line pharmacological intervention for severe mental illnesses (SMI) such as schizophrenia (1) and other psychoses, while also being used to relieve distress and to treat neuropsychiatric symptoms in dementia (2). Oral antipsychotic medication prescribed in primary care is one of the main sources of support to people with a history of psychosis.…”
Section: Introductionmentioning
confidence: 99%